Reduced‐intensity conditioning allogeneic transplantation after salvage treatment with DT‐PACE in myeloma patients relapsing early after autologous transplant. (20th July 2017) - Randall, Kate; Kaparou, Maria; Xenou, Evgenia; Paneesha, Shankara; Kishore, Bhuvan; Kanellopoulos, Alexandros; Lovell, Richard; Holder, Kathy; Suhr, Julie; Baker, Lynda; Ryan, Lynn; Nikolousis, Emmanouil
Abstract: Objective: In this retrospective single‐centre study, we have looked into the transplant outcomes(overall survival OS, progression‐free survival PFS, GvHD) and the role of chimerism, DLI and pretransplant characteristics in patients who had a suboptimal response (<12 months) to an autologous stem cell transplant for myeloma and underwent an alemtuzumab T‐cell depleted reduced‐intensity allograft(RIC). Methods: Twenty‐four patients were salvaged with two cycles of DT‐PACE and received a RIC transplant with fludarabine, melphalan and alemtuzumab. All the patients received PBSC grafts, eight patients had a sibling donor, and 16 had a graft from a fully matched unrelated donor. The median follow‐up was 65.3 months (6‐132 months). Results: The median overall survival was 55.4 months. DLI administration was associated with a trend towards better overall survival ( P =.05). Disease status at allo‐HCT, PR or VGPR, ISS score and CMV serostatus was not significant predictors of OS and PFS. Full donor whole blood chimerism (≥98%) at 3 months post‐transplant was associated with PFS ( P =.04) but did not have a significant impact on OS( P =.45). Conclusion: Reduced‐intensity alemtuzumab‐conditioned allograft for myeloma after DT‐PACE salvage chemotherapy is an efficient and low toxicity treatment for those who had a suboptimal response postautologous stem cell transplant for myeloma.